The fickle Mutation of a Cytoplasmic Tyrosine Kinase Effects Sensitization but not Dishabituation in Drosophila Melanogaster - Asztalos, Zoltan (Informa Healthcare, 2007)
fickle is a P-element mutation identified from a screen for defects in courtship behavior and disrupts the fly homolog of Bruton's tyrosine kinase (Btk) gene (Baba et al., 1999). Here, we show that habituation of the olfactory jump reflex also is defective in fickle. Unlike, the prototypical memory mutants, rutabaga and dunce, which habituate more slowly than normal, fickle flies habituate faster than normal. fickle's faster-than-normal response decrement did not appear to be due to sensorimotor fatigue, and dishabituation of the jump response was normal. Based on a long-standing “two opponent process” theory of habituation, these data suggested that behavioral sensitization might be defective in fickle. To test this hypothesis, we designed a olfactory sensitization procedure, using the same stimuli to habituate (odor) and dishabituate (vortexing) flies. Mutant flies failed to show any sensitization with this procedure. Our study reveals a “genetic dissection” of sensitization and dishabituation and, for the first time, provides a biological confirmation of the two opponent process theory of habituation.